Kinetic Study of Bentonite-Based Desulphurisation for Cleaner Kerosene - Haider J. Esmaeel; Safaa M.R. Ahmed (Platform, a Journal of Engineering)
This study introduces a novel, non-extractive Oxidative Desulphurisation (ODS) method for kerosene using a three-phase Oscillatory Baffled Reactor (OBR). The process utilises commercial bentonite clay (aluminium silicate hydrate) loaded with 15 wt% vanadium pentoxide (V₂O₅) as a cost-effective catalyst. Catalyst characterisation showed surface areas of 56 m²/g for bentonite and 50.13 m²/g for the V₂O₅/bentonite composite. Structural and thermal properties were analysed using X-ray diffraction (XRD). The ODS process was tested under various conditions, including temperatures (40–80°C), residence times (15-120 min), oscillation intensities (63.79–382.8 Reo), and sulphur concentrations (84.4–578 ppm). The optimal result, 81.73% sulphur removal, was achieved at 50°C, 578 ppm sulphur, and Reo = 382.8. Kinetic analysis revealed a second-order reaction with a low activation energy of 46.39 kJ/mol for dibenzothiophene (DBT) oxidation. Unlike previous studies that relied on synthetic or metal-heavy catalysts, this research highlights the effectiveness of a natural, low-cost bentonite-based catalyst. It offers a sustainable pathway for cleaner fuel production and contributes valuable insights into reaction mechanisms and kinetics, supporting future scale-up of eco-friendly desulphurisation technologies.